Deriving improved plasma fluid equations from collisional kinetic theory - Dimant, Y. S. (Frontiers in Astronomy and Space Sciences, 2024)
IntroductionDeveloping a quantitative understanding of wave plasma processes in the lower ionosphere requires a reasonably accurate theoretical description of the underlying physical processes. For such a highly collisional plasma environment as the E-region ionosphere, kinetic theory represents the most accurate theoretical description of wave processes. For the analytical treatment, however, collisional kinetic theory is extremely complicated and succeeds only in a limited number of physical problems. To date, most research has applied oversimplified fluid models that lack a number of critical kinetic aspects, so the coefficients in the corresponding fluid equations are often accurate only to an order of magnitude.MethodsThis paper presents a derivation for the highly collisional, partially magnetized case relevant to E-region conditions, using methods of the collisional kinetic theory with a new set of analytic approximations.ResultsThis derivation provides a more accurate reduction of the ion and, especially, electron kinetic equations to the corresponding 5-moment fluid equations. It results in a more accurate fluid model set of equations appropriate for most E-region problems.DiscussionThe results of this paper could be used for a routine practical analysis when working with actual data. The improved equations can also serve as a basis for more accurate plasma fluid computer simulations.